TINA for services and advanced signaling and control in nextgeneration networks. - Mampaey, M. (IEEE Communications magazine)
This article describes solutions that use the Telecommunications Information Networking Architecture and its advanced service architecture and call model, for the definition of services and advanced signaling and control in next-generation networks. It presents both the solutions for extending traditional signaling and/or interacting and interworking with it, and the way the TINA service architecture can constitute an intelligent service platform providing multiple value-added services to the PSTN and the Internet. In each case, the article provides details and examples to demonstrate the case and illustrate the solutions for trendy technologies such as mobile and the Internet